Comparison of emotional and social intelligence assessment of students in state and private school during the pandemic - Akif Khilmiyah (Graduate School, Universitas Negeri Yogyakarta, 2021)
This study aims to determine differences in emotional and social intelligence assessment between public and private school students using Android-based PKES (Penilaian Kecerdasan Emosional-Sosial or Social-Emotional Intelligence Assessment) application in strengthening student character during the pandemic. This survey study with a quantitative approach was analyzed using a comparative model. The subjects were 120 parents and students of public and private elementary schools in Yogyakarta chosen by purposive sampling. Data were collected through interviews, observations, and Likert scale tests with the PKES application and analyzed by t-test. It reveals that state elementary school students' emotional and social intelligence emphasizes the psychomotor aspect or good behavior with the habituation method. Meanwhile, private elementary school students emphasize the cognitive aspect of character knowledge through the lecture method. The affective aspect of social-emotional intelligence in public and private elementary schools is still low. Students have not been trained to feel the good character impact with various methods, so good behavior will not last until they are old because it has not been embedded in their hearts. Different tests with t-test obtained 0.3780.05, so the difference is insignificant. The emotional and social intelligence of public and private elementary school children during the pandemic is not much different. Because students study at home during the pandemic, their character is more influenced by parents than teachers. It implies that parents and teachers should more often train students to feel happy doing good deeds, so good character is embedded in the heart and lasts for a long time.